Evaluation of hydroxychloroquine as a perpetrator on cytochrome P450 (CYP) 3A and CYP2D6 activity with microdosed probe drugs in healthy volunteers - Stoll, Felicitas E.; Blank, Antje; Mikus, Gerd; Czock, David; Weiß, Johanna; Meyer-Tönnies, Marleen J.; Gümüs, Katja S.; Tzvetkov, Mladen Vassilev; Burhenne, Jürgen; Haefeli, Walter E. (European journal of drug metabolism and pharmacokinetics, 2024)
Background and Objective Although polypharmacy is a particular challenge in daily rheumatological practice, clinical research on the effects of hydroxychloroquine (HCQ), a commonly used drug for patients with rheumatic diseases, is sparse on cytochrome P450 (CYP)-mediated metabolism. We have shown that pre-treatment with pantoprazole does not alter HCQ absorption in healthy volunteers. In this paper, we report the effects of a single 400 mg dose of HCQ on specific CYP3A and CYP2D6 substrates in healthy volunteers.Methods In the trial, participants were randomized into two groups (HCQ plus a 9-day course of pantoprazole, or HCQ only). As a secondary endpoint, the effects of a single oral dose of HCQ on the exposure of the oral microdosed CYP3A probe drug midazolam (30 mu g) and the oral microdosed CYP2D6 probe drug yohimbine (50 mu g) were studied in 23 healthy volunteers (EudraCT no. 2020-001470-30, registered 31 March 2020).Results The exposure of the probe drugs after intake of HCQ compared with baseline values was quantified by the partial area under the plasma concentration-time curve 0-6 h after administration (AUC(0-6 h)) for yohimbine and the partial AUC(2-4 h) for midazolam. Under HCQ, yohimbine AUC(0-6 h )was unchanged, independent of CYP2D6 genotypes and pantoprazole exposure. Midazolam AUC(2-4 h )was 25% higher on the day of HCQ administration than at baseline (p = 0.0007). This significant increase was driven by the pantoprazole subgroup, which showed a 46% elevation of midazolam AUC(2-4 h) as compared with baseline (p < 0.0001). The ratio of midazolam to 1-OH-midazolam partial AUC(2-4 h) significantly increased from 3.03 +/- 1.59 (baseline) to 3.60 +/- 1.56 (HCQ) in the pantoprazole group (p = 0.0026).Conclusion In conclusion, we observed an increased midazolam exposure most likely related to pantoprazole.